Mewujudkan Perilaku Toleran Pada Pendidikan Anak Usia Dini Perspektif Islam Moderasi - Tumpal Daniel (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2019)
Data shows that radical groups in Indonesia are currently dominated by young people who tend to understand religious teachings textually. Most radical groups in Indonesia are filled with young and male people and their religious understanding tends to be textual, this is also an urban phenomenon. So at a young age who are still looking for identity it is indeed quite vulnerable, because it needs to be balanced with religious information that contain tolerance values.Moderate Islam-based character education is very necessary since early childhood to establish habituation, formation of mindset, and how they perceive a difference. The establishment of a tolerant attitude should start from the closest family member because of the first interaction a child has in the family environment. Tolerance must be done early, the sensitivity of a child in establishing relationships and communication with a pluralistic environment must become habituation. The main purpose of education is to produce a human personality that is mature intellectually, emotionally and spiritually, so the school has a moral responsibility to educate children to be smart in accordance with the expectations of parents and society.